Use of radiopharmaceuticals in the diagnosis of neurodegenerative diseases - Anna Tempesta; Anna Tolomeo; Azzurra Stefanucci; Lorenza Marinaccio; Adriano Mollica (European Journal of Medicinal Chemistry Reports)
Neurodegenerative diseases are illnesses that affect the central nervous system (CNS) characterized by a series of symptoms such as dementia, motor disturbances, behavioural and psychological disorders, and cognitive impairments. The most common neurodegenerative disorders are Alzheimer's disease and Parkinson's disease, for which radiopharmaceuticals have been developed and approved for the purpose of PET investigation. Biomarkers are molecules that can be studied and used for diagnostic purposes, to monitor diseases, and to identify potential risk factors early.